Acute exercise increases circulating IGF-1 in Alzheimer's disease patients, but not in older adults without dementia - Stein, Angelica Miki [UNESP]; da Silva, Thays Martins Vital [UNESP]; Coelho, Flávia Gomes de Melo [UNESP]; Rueda, André Veloso; Camarini, Rosana; Galduróz, Ruth Ferreira Santos [UNESP] (Elsevier, 2021)
Objectives: Increased Insulin-like growth factor I (IGF-1) has been associated with improvement of cognitive function in response to exercise. Evidences indicate a role for IGF-1 in beta-amyloid clearance and reducing hyperphosphorylation tau in Alzheimer's disease (AD). There is a need to investigate the IGF-1 response to exercise in AD patients due to well-known potential effects of exercise on IGF-1. The aim of this study was to examine circulating IGF-1 levels in AD patients and older adults without dementia after acute exercise and to verify the associations among cardiorespiratory fitness, cognition and IGF-1 levels. Method: Seventy-four older adults (40 older adults without dementia and 34 AD patients) participated in this study. The outcomes included IGF-1 plasma levels and performance in the submaximal exercise stress test. Secondary outcomes included cognitive functions, depressive symptoms, level of physical activity, insulin-resistance, and cholesterol. All participants performed the incremental test on a treadmill and IGF-1 was collected before and after the exercise. Results: A tendency to the difference of baseline IGF-1 plasma levels between the groups was found. After the acute exercise AD patients also presented higher levels of circulating IGF-1 compared to the Older adults without dementia. Correlations among cardiorespiratory fitness and cognitive functions were found. Conclusion: The findings suggest that AD patients and older adults respond differently to acute exercise in terms of circulating IGF-1 levels. This response seems to indicate either an IGF-1 resistance or a compensatory exercise-induced to lower IGF-1 levels in AD patients. Cardiorespiratory fitness is associated with global cognition, executive function, attention and information processing speed.
Keywords: Alzheimer's disease; Dementia; Exercise; Insulin-like growth factor I